Influence of Media Concentration Plant and Fertilizer Grow Against Quick S Hybrid Dendrobium Orchid Plant Growth: Pengaruh Media Tanam dan Konsentrasi Pupuk Grow Quick S Terhadap Pertumbuhan Tanaman Anggrek Dendrobium hybrid - Abdul Rofik (Agrifarm : Jurnal Ilmu Pertanian, 2015)
Effect of growing media and fertilizers Grow Quick S concentration on the growth of Dendrobium orchid hybrid. The aim of research to determine the effect of growing media and fertilizers Grow Quick S on the growth of orchids. Research compiled in Aak Design (RBD) with 3 x 4 factorial analysis and repeated 3 times. The first factor is the planting medium (M) which consists of three levels, namely: (m1; m2 coconut husk; charcoal and m3; brick) and the second factor Quick Grow fertilizer S (P), which consists of 4 levels, namely: ( p0; 0 ml / liter of water, p1; 1 ml / liter of water, p2; 2 ml / liter of water and p3; 3 ml / liter of water). The results showed growing media treatment significantly affected all variables observed except in the number of leaves ages of 30 and 60 HST and the increase in diameter trunk age of 30 HST. The best treatment is achieved m1 (coco) Quick Grow S treatment significantly affected all variables observed except in the number of leaves ages of 30 and 60 HST and the increase in diameter trunk age of 30 HST. Interaction of the two treatments did not affect significantly affected all variables observed. Keywords: Dendrobium orchid hybrid, growing media and Quick Grow S